2005
DOI: 10.2166/wh.2005.048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weather and river flow on cryptosporidiosis

Abstract: Outbreaks of cryptosporidiosis have been linked to weather patterns such as heavy precipitation. However, outbreaks only account for a small percentage of all cryptosporidiosis cases and so the causes of the majority of cases are uncertain. This study assessed the role of environmental factors in all cases of cryptosporidiosis by using ordinary least-squares regression to examine the relationship between the monthly cryptosporidiosis rate, and the weather and river flows in England and Wales between 1989 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 19 publications
4
72
0
Order By: Relevance
“…An outbreak of giardiasis in Montana (USA) was related to excess rainfall [39]. Cryptosporidiosis cases in England and Wales were positively associated with maximum river flow [45]. Escherichia coli O157:H7 and Campylobacter jejuni were responsible for a waterborne outbreak, causing 7 deaths, 65 hospitalization and more than 2300 cases of gastrointestinal illness in the Canadian town of Walkerton [46].…”
Section: Heavy Rainfall and Floodsmentioning
confidence: 99%
“…An outbreak of giardiasis in Montana (USA) was related to excess rainfall [39]. Cryptosporidiosis cases in England and Wales were positively associated with maximum river flow [45]. Escherichia coli O157:H7 and Campylobacter jejuni were responsible for a waterborne outbreak, causing 7 deaths, 65 hospitalization and more than 2300 cases of gastrointestinal illness in the Canadian town of Walkerton [46].…”
Section: Heavy Rainfall and Floodsmentioning
confidence: 99%
“…High levels of rainfall onto saturated soil could plausibly facilitate the transfer of Cryptosporidium oocysts in animal manure into surface water (Lake et al 2005;Thurston-Enriquez et al 2005).…”
Section: One Of the Main Routes Of Transmission Ofmentioning
confidence: 99%
“…Sewage overflow during high levels of rainfall could also lead to Cryptosporidium oocysts and Giardia cysts contaminating water used for recreation or drinking (Lake et al 2005). In several studies rainfall has been found to be positively correlated with the concentration of Cryptosporidium oocysts and/or Giardia cysts in surface and runoff water (Atherholt et al 1998;Thurston-Enriquez et al 2005;Arnone & Walling 2006;Miller et al 2007).…”
Section: One Of the Main Routes Of Transmission Ofmentioning
confidence: 99%
“…Heavy precipitation has been linked to a number of drinking-water outbreaks of Cryptosporidium (a pathogen causing a diarrhoeal illness) in Europe, due to spores infiltrating drinking water reservoirs from springs and lakes and persisting in the water distribution system (Lake et al, 2005;Semenza and Nichols, 2007). In Germany, bacteriological and parasitic parameters spiked considerably during extreme runoff events (Kistemann et al, 2002).…”
Section: Past Trendsmentioning
confidence: 99%